Methodology of education through research in training fundamental teaching teachers -early years: in practice and possibilities - Estevam Silvano, Geanne Estevam Silvano Geanne; Santos, Geovar Miguel dos; Morais, Ione Rodrigues Diniz; Garcia, Tânia Cristina Meira (Revista Ensino de Geografia (Recife), 2020)
The present work tries to present the application of the Methodology of Educating through Research as a possibility of teaching in the early years of Elementary Education whose focus is research in the classroom. This widespread proposal and which served as an evaluative requirement at the end of the semester in the disciplineGeography in the School Space of the Professional Master in Geography at UFRN -GEOPROF / CERES-RN in semester 2019.2, the study of research as an educational principle, linked to the theme Geography and Citizenship correlates the fundamentals defended by Pedro Demo in the search to encourage its use also in Basic Education by the master's students. Exploratory research used field research questionnaires to situate / diagnose 5th year students' knowledge about essential services in the neighborhood where they study. As a theoretical basis, research of the analytical descriptive type, through bibliographic study, based on authors of the socio-cultural pedagogical approach, in pedagogical didactic term, various strategies to achieve the objectives